Synthesis of 2-Arylpyrazolo[1,5-a]pyridines by Suzuki–Miyaura Cross-Coupling Reaction - Umei, Kentaro; Nishigaya, Yosuke; Kamiya, Megumi; Kohno, Yasushi; Seto, Shigeki (Synthesis, 2015)
Convenient access to a variety of 2-arylated pyrazolo[1,5-a]pyridine via pyrazolo[1,5-a]pyridine-2-yl triflate using the Suzuki–Miyaura cross-coupling reaction is described. Fifteen 2-arylpyrazolo[1,5-a]pyridine derivatives were synthesized in 52–95% yields.
Keywords: Suzuki–Miyaura cross-coupling reaction; 2-arylpyrazolo[1,5-a]pyridine; triflate; regioselectivity; medicinal chemistry